Atom probe tomography assessment of the impact of electron beam exposure on InxGa1-xN/GaN quantum wells - Bennett, S.; Saxey, David; Kappers, M.; Barnard, J.; Humphreys, C.; Smith, G.; Oliver, R. (2011)
This study addresses the ongoing debate concerning the distribution of indium in InxGa1−xN quantum wells(QWs) using a combination of atom probe tomography (APT) and transmission electron microscopy(TEM). APT analysis of InxGa1−xN QWs, which had been exposed to the electron beam in a TEM, revealed an inhomogeneous indium distribution which was not observed in a control sample which had not been exposed to the electron beam. These data validate the effectiveness of APT in detecting subtle compositional inhomogeneities in the nitrides.